PHYSIOLOGICAL QUALITY OF WHEAT SEEDS IN RESPONSE TO APPLICATION OF AZOSPIRILLUM BRASILENSE AND HUMIC ACID - Cotrim, M. F.; Alvarez, R. C. F.; Seron, A. C. C. (Revista Brasileira de Engenharia de Biossistemas, 2016)
This study aimed to evaluate the effect of the application via Azospirillum brasilense seed and humic acid on physiological quality of wheat seeds. The treatments were: control, inoculation of bacteria Azospirillum brasilense (AZO), application of humic acid (HA) and AZO + AH association. The seeds were submitted to germination, first count, accelerated aging, cold test, root length and shoot and root dry mass and shoot. The design was completely randomized in a 2x4 factorial design (two cultivars and four treatments) with four replications. It was concluded that the AZO and AH isolated, did not affect the germination of wheat seeds, however, inoculation via AZO seed promotes benefit in force, providing greater resistance to seeds when exposed to adverse conditions of high temperature and humidity, in However, this effect depends on the cultivar. The application of AH and AH + AZO association benefits the growth and dry weight mass of shoots of wheat seedlings.